Study reporting the lessons learned from implementing the Kenya Livestock Insurance Program (KLIP) with the goal of building financial resilience in pastoral communities in Africa - CGIAR Research Program on Livestock (2020)
The success story of KLIP has triggered a strong interest from national governments across the IGAD region toward scaling index-insurance for livestock regionally.